1999
DOI: 10.4269/ajtmh.1999.61.375
|View full text |Cite
|
Sign up to set email alerts
|

Short report: high prevalence and imbalanced age distribution of the Plasmodium falciparum dihydrofolate reductase gene Asn108 mutation in an area of low pyrimethamine usage in Nigeria.

Abstract: Abstract. Resistance of Plasmodium falciparum to pyrimethamine is associated with a non-silent point mutation of the parasite dihydrofolate reductase (DHFR) gene (Ser 108 → Asn 108 ). Wide-scale use of antimalarials is thought to contribute to the emergence of drug resistance. In 131 P. falciparum-infected children in rural Nigeria, the frequency of the resistant Asn 108 genotype was assessed by enzymatic restriction digestion of polymerase chain reaction-amplified DHFR sequences and compared with residual pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
(10 reference statements)
0
8
1
Order By: Relevance
“…Asn-108 frequency was 60% in the 0-2 age group and 18% among children age 6 and over. 26 However, our analysis of Colombian samples-in contrast to the Nigerian study-did not find a decline in the frequency of Asn-108 with an increase in the age of the group studied. Nor was it possible to establish a statistically significant relationship between children's ages and presence of the Ser-108 genotype or the presence of mixed infections ( 2 ‫ס‬ 8,91).…”
Section: Discussioncontrasting
confidence: 48%
“…Asn-108 frequency was 60% in the 0-2 age group and 18% among children age 6 and over. 26 However, our analysis of Colombian samples-in contrast to the Nigerian study-did not find a decline in the frequency of Asn-108 with an increase in the age of the group studied. Nor was it possible to establish a statistically significant relationship between children's ages and presence of the Ser-108 genotype or the presence of mixed infections ( 2 ‫ס‬ 8,91).…”
Section: Discussioncontrasting
confidence: 48%
“…However, age distribution was also a noticeable difference; GP participants were mostly children <15 years of age, whereas pregnant women were aged 15–45 years. In children, age has been shown to be inversely related to dhfr S108 and quintuple mutation prevalence [42, 43]. Nevertheless, the difference in prevalence of dhfr N51 and triple dhfr mutations compared with ANC samples remained even if only GP participants aged 15–45 years were included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, young non-immune children suffer repeated symptomatic episodes, undergo consecutive drug treatment, and are more likely to carry drug-resistant parasites. Corroborating this hypothesis, studies in areas of high malaria transmission found that prevalence of SP resistance markers declines with age 64,65 and that quintuple mutants are more prevalent in children under five years of age than in older children 66 . Conversely, prevalence of resistance mutations may not vary by age in areas of low or unstable malaria transmission with less immunity, as was observed when comparing children under and over the age of 4 years in Northern Tanzania 59 .…”
Section: Children and Smc/iptcmentioning
confidence: 95%